(untitled) (Revista Educação, Artes e Inclusão, 2023)
The article proposes to analyze two collective teaching methods for bow instruments. In the last few years, we have seen significant growth in relation to the use and research of collective teaching of musical instruments in our country, but when the string teacher seeks to carry out his work using a method that uses Brazilian repertoire, he finds many problems, because there are few, if any, options on the market, which also have no tradition in the commercialization of music teaching materials. Specifically, the proposal was to carry out an analysis focused on technical and cultural issues, which used the guide-oriented notation procedure for data collection and, in the interpretation, organization and presentation of the data obtained, descriptive statistics and the pattern matching process. The two methods analyzed in this article can contribute to enrich the initial process of teaching music, offering a good option to include the Brazilian repertoire, formed by songs and folk themes, in the initiation of students of violin, viola, cello and double bass.